2003
DOI: 10.1136/jcp.56.8.575
|View full text |Cite
|
Sign up to set email alerts
|

Increase of bone marrow lymphocytes in systemic mastocytosis: reactive lymphocytosis or malignant lymphoma? Immunohistochemical and molecular findings on routinely processed bone marrow biopsy specimens

Abstract: Aims: To clarify the nature (reactive or neoplastic) of lesional, perifocally aggregated lymphocytes in bone marrow infiltrates of systemic mastocytosis (SM), the histopathology of which can resemble malignant lymphoma with focal bone marrow involvement, particularly low grade malignant B cell lymphoma of lymphoplasmacytic immunocytoma subtype, which frequently exhibits increased mast cell (MC) numbers. Methods: Thirteen cases of SM and three of lymphoplasmacytic immunocytoma with predominant focal bone marrow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 13 publications
3
15
0
Order By: Relevance
“…Bone marrow infiltrates may be pure mastocytic, mixed mastocytic/lymphocytic or predominantly lymphocytic. The immunohistochemical and molecular studies revealed that the lymphoid infiltration associated with SM is an admixture of T and B lymphocytes or predominantly T-cells and is polyclonal and reactive in nature [6,10]. However in cases with a predominant Bcell infiltration, a diagnosis of low-grade non-Hodgkin lymphoma is often suspected initially, as in our case [6,12].…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Bone marrow infiltrates may be pure mastocytic, mixed mastocytic/lymphocytic or predominantly lymphocytic. The immunohistochemical and molecular studies revealed that the lymphoid infiltration associated with SM is an admixture of T and B lymphocytes or predominantly T-cells and is polyclonal and reactive in nature [6,10]. However in cases with a predominant Bcell infiltration, a diagnosis of low-grade non-Hodgkin lymphoma is often suspected initially, as in our case [6,12].…”
Section: Discussionmentioning
confidence: 94%
“…Histologically, the infiltration is often focal and dense, especially in the forms that show a malignant course, the MCs are morphologically abnormal and lack metachromatic granules [5,7,13]. Another reason of misdiagnose, is that the underlying histological picture of the bone marrow might be complicated by secondary hematological disorders [3,4,6,[8][9][10]12]. Moreover, it is known that the infiltrates are not composed exclusively of MCs, but also contain eosinophils and lymphocytes [10].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations